Soft fibrin matrix downregulates DAB2IP to promote Nanog-dependent growth of colon tumor-repopulating cells - Zhang, Meng; Xu, Cong; Wang, Hai-zhou; Peng, Ya-nan; Li, Hai-ou; Zhou, Yun-jiao; Liu, Shi; Wang, Fan; Liu, Lan; Chang, Ying; Zhao, Qiu; Liu, Jing (Cell death & disease, 2019)
Colon cancer stem cells (CSCs) have been shown to be responsible for the recurrence and metastasis of colorectal cancer (CRC). As a crucial microenvironmental factor, extracellular matrix (ECM) stiffness is known to affect the stemness of CSCs. Recently, fibrin deposition in the stroma of CRC was demonstrated to be responsible for tumor development. In this study, we used salmon fibrin gel to provide a 3D ECM for colon cancer cells and investigated its effects on cell growth as well as the underlying mechanisms. Compared with stiff 420 Pascal (Pa) and 1 050 Pa gels, 90 Pa soft fibrin gel was most efficient at isolating and enriching tumor colonies. The size and number of colony formation negatively correlated with gel stiffness. Specifically, these tumor colonies exhibited efficient tumorigenicity, upregulated stem cell markers, and had anti-chemotherapeutic properties and were thus named tumor-repopulating cells (TRCs). More importantly, the self-renewal molecule Nanog was sharply induced in 3D-cultured colon TRCs; further, Nanog siRNA significantly inhibited colony formation, suggesting the indispensable role of Nanog in TRC growth. A subsequent mechanistic study illustrated that Nanog expression could be modulated through fibrin gel stiffness-induced DAB2IP/PI3K/FOXA1 signaling in colon TRCs.